Погляди митрополита Антонія (Храповицького) щодо проблеми "українізації" православної церкви (1917-1920 рр.) - Телуха, Світлана Степанівна (НТУ "ХПІ", 2014)
В статті проаналізовано погляди і судження відомого церковного діяча та богослова митрополита Антонія (Храповицького) щодо "українізації". Обґрунтовано позицію Владики щодо вживання української мови на державному рівні. Вказано на особливості сприйняття митрополитом Антонієм української мови в церковному житті. Висвітлено негативне відношення Антонія (Храповицького) до будь-яких спроб проникнення української мови в церковне богослужіння та вказане підґрунтя подібних його суджень.

During the revolutionary events of 1917-1920. Ukraine intensified various national movements. Church and church life are also imbued with national trends. Questions about "ukrainianization" church services, publishers of liturgical books in Ukrainian language became actively discussed at various meetings of the Orthodox clergy of the diocese of Kharkiv. Attention is paid to the analysis of the views and judgments of the Ukrainian issue known church leader and theologian, Metropolitan Anthony (Khrapovitsky). In the article there are historical data that allow you to objectively judge the conduct of policy ukrainianization in church. An important place in the study takes a position on the introduction of Antony of the Ukrainian language during worship, namely its categorical rejection of such a policy. The article presents the different quotes of Metropolitan Anthony and explanation of his thoughts on this issue, with regard his views with the general trends in Orthodoxy.
Metropolitian Antony (Khrapovitsky) views of the "Ukrainization" Orthodox Church
Keywords: українізація; українська мова; митрополит Антоній (Храповицький); Харківська єпархія; церковне життя; богослужіння; ukrainization; Ukrainian language; Metropolitan Anthony (Khrapovitsky); Kharkov diocese; church life; ukrainization worship